FORMATION OF ETHNIC IDENTITY OF THE PERSONALITY (PSYCHOLOGICAL ASPECT) - Anna Sergeevna Sobilskaya (Вестник Северо-Кавказского федерального университета)
In article the main tendencies of understanding of ethnicity, ethnic identity of the personality, the ethnocultural personality are reflected. In article the question of relevance of application of psychological technologies on formation of ethnic identity of the personality is considered. The main tendencies of application of psychological technologies are considered.